2H-SiC films grown by laser chemical vapor deposition. Issue 16 (December 2015) - Ito, Akihiko; Kanno, Hitoshi; Goto, Takashi
Abstract: We demonstrated the synthesis of 2H-SiC films on graphite and (0001) sapphire substrates by laser chemical vapor deposition. A tris(dimethylamino) silane was used as a novel precursor for the synthesis of SiC films in a CH4 atmosphere. The 2H-SiC films were obtained at a deposition temperature of 920 K on the sapphire substrate. The films comprised a -axis-oriented columnar grains and their in-plane orientation relationship was [1000] 2H-SiC // [0001] sapphire and [0001] 2H-SiC // [1000] sapphire. The films were deposited at the rate of 182 μm h −1 .